Program PDS Berkelanjutan dalam Pembelajaran Sintaksis Bahasa Indonesia Berbasis KKNI di STKIP Muhammadiyah Kotabumi - Nur Mei Ningsih (Universitas Muhammadiyah Kotabumi, 2019)
Program Penugasan Dosen di Sekolah (PDS) gives experience for the lecturers to understand comprehensively students’ characteristics in learning process. The learning process applied at STKIP Muhammadiyah Kotabumi based on KKNI-Dikti based curriculum with the characteristics which are interactive, holistic, integrative, saintific, contextual, them atic, collaborative, and student-centered. Indonesian syntax course focused on the students or how the students learn and understand the concept of material as well as implement it based on the concept understood. The method used in this article is descriptive method and qualitative approach in which describing the condition of fourth semester students in Indonesian syntax course. Based on the finding it was found that 88% students were active, creative and enthusiastic in learning process because the method and learning model are varied. It made the students to be more interested and active in following the learning. Meanwhile, 12 % students were active and motivated to learn. It can be concluded that the sudents’ achievement was increased.